2006
DOI: 10.1159/000092834
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Kaposi’s Sarcoma Restricted to the Site of a Previous Deep Venous Thrombosis: Abrupt Onset after Withdrawal of Sirolimus

Abstract: Kaposi’s sarcoma (KS) is an angioproliferative neoplasia associated with human herpesvirus 8 (HHV-8) infection. HHV-8 generates KS by means of the secretion of vascular endothelial growth factor (VEGF) andup-regulation of VEGF receptor, KDR, in endothelial cells. We report a case of KS in a 72-year-old male with a renal transplant who had received immunosuppressant drugs including sirolimus, mycophenolate mofetil, tacrolimus and steroids. KS developed 11 months after transplantation, in relation to deep venous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
9
0
2
Order By: Relevance
“…Patient 1 had iatrogenic KS but skin manifestations did not improve when the immunosuppressant dose was halved. However, in this case the reduction of immunosuppressive treatment could already explain the improvement of KS observed, sometimes delayed until after the interruption of the immunosuppressive drug [20]. Although our series of non-AIDS-related KS patients was small, our results seem to confirm the effectiveness and relative safety of thalidomide treatment as already found in AIDS-related KS [15, 16].…”
Section: Discussionsupporting
confidence: 77%
“…Patient 1 had iatrogenic KS but skin manifestations did not improve when the immunosuppressant dose was halved. However, in this case the reduction of immunosuppressive treatment could already explain the improvement of KS observed, sometimes delayed until after the interruption of the immunosuppressive drug [20]. Although our series of non-AIDS-related KS patients was small, our results seem to confirm the effectiveness and relative safety of thalidomide treatment as already found in AIDS-related KS [15, 16].…”
Section: Discussionsupporting
confidence: 77%
“…Is DVT associated with KS? In the literature, there are two case reports where a DVT preceded the development of KS as with our patient 10. In conclusion, our patient presented with KS despite having a high CD4 count and suppressed viral load, which may have been explained by cofactors such as DM, not smoking and a previous DVT.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, regression of visceral KS after conversion to sirolimus has also been reported, with complete regression of visceral and cutaneous lesions occurring in a transplant recipient within a few months of conversion [14]. In accordance with these data, abrupt onset of KS was reported in a renal transplant recipient following the withdrawal of sirolimus [15]. Recent studies have suggested a possible mechanism for the action of PSIs on preventing angiogenesis in tumours [5].…”
Section: Conversion To Proliferation Signal Inhibitorsmentioning
confidence: 57%